KEANEKARAGAMAN DAN KELIMPAHAN SERANGGA ORDO COLEOPTERA DI TEPIAN SUNGAI MUSI KOTA PALEMBANG SEBAGAI SUMBANGAN MATERI PADA MATA KULIAH ENTOMOLOGI DI PENDIDIKAN BIOLOGI FKIP UNIVERSITAS SRIWIJAYA - Riyanto Riyanto (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2016)
Abstract:The rTop of Formesearchof diversity and abundance of the order Coleoptera on the riparian of the Musi river Palembang have been done. This study aims to determine the diversity and abundance of the order Coleoptera on the riparian of the Musi river in Palembang. The method used is a survey method. Determining the location and station of research conducted by purposive sampling method. Sampling the species of the order Coeloptera done by direct sampling, insect nets and traps insects. Samples were analyzed using species diversity index, relative abundance index, dominance index and evenness index. The results were found 437 individuals, 29 species and 12 families of the order Coleoptera. Family of the order Coleoptera, namely Carambycidae, Carabidae, Chrysomilidae, Ciidae, Coccinellidae, Curculionidae, Dystiscidae, Melandryidae, Phalacridae, Scarabidae, Staphylinidae, and Tenebrionidae. The family of Coccinellidae and Chrysomilidae have the highest number of species, namely 8 species. The highest number of individuals was found in the family Chrysomilidae of survey sites Sungai Ijuk, which is a species Lema diversa (114 individuals). Based on the survey area the highest individual number of the order Coleoptera found in the Sungai Ijuk (451 individuals). The species diversity of Coleoptera on the riparian of the Musi riverin Palembang different. Diversity index of insect order Coleoptera in four locations in Palembang Musi riverriparian classified as moderate or not so diverse. Evenness index of the order Coleoptera in four survey sites Palembang Musi river riparian lower means quite evenly. Dominance index species of the order Coleoptera on the riparian of Musi River in Palembang showed the value of <0.50, meaning do not happen dominance of certain species. The information of this research results is expected to be the initial information diversity and abundance of the order Coleoptera on the riparian of the Musi river Palembang. Bottom of Form Key Words: Biodiversity,Â  Coleoptera, Musi River